Perencanaan Manajemen Pemeliharaan Komponen Arsitektur dan Utilitas Pada Gedung Asrama LPMP Sumatera Barat - Hendra Alexander; Riswandi Riswandi; Satwarnirat Satwarnirat; Muhammad Elan Aqsa (Jurnal Ilmiah Rekayasa Sipil, 2022)
The use of the building is to support activities or as infrastructure for building owners or building users in optimally carrying out their daily activities. The building is expected to be flexible following the flow of changes that occur in the activities of building owners or users later. This is what underlies the need for building maintenance activities. In the LPMP Dormitory building, maintenance activities have not been managed properly. In order for maintenance activities to be better, a maintenance management plan is made on the architectural and utility components for the building. Starting from listing the components that are maintained, then making maintenance classifications of these components, namely preventive maintenance and corrective maintenance. Next, make standard operating procedures for each of these components, complete with a flow chart and checklist form. Scheduling is also an important point in maintenance activities, starting from scheduling daily, weekly, monthly, and yearly components. The total preventive maintenance cost for architectural and utility components in the building is Rp. 303,648,000. This fee is the maintenance fee for one year.